2006
DOI: 10.1038/nmat1607
|View full text |Cite
|
Sign up to set email alerts
|

Local density of states effects at the metal-molecule interfaces in a molecular device

Abstract: Clarifying the nature of interactions between metal electrodes and organic molecules still represent one of the challenging problems in molecular electronics that needs to be solved in order to optimize electron transport through a molecular device. For this purpose, electronic properties at metal-molecule interfaces were studied by combining experimental and theoretical methods. Applying a novel electrochemical approach, strictly two-dimensional Pd islands were prepared on top of 4-mercaptopyridine self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(158 citation statements)
references
References 46 publications
10
146
2
Order By: Relevance
“…In situ STM has also been employed to characterize the structure of the electrodeposited Pd on the 4-ATP adlayer, as shown in Figure 2c. Like in former studies on Pd overlayers on top of 4-mercaptopyridine SAMs, [7,8,13,14] monoatomic height islands are seen in line-scans (not shown here), which finally can be assigned to Pd islands on top of the 4-ATP adlayer (see below). However, unlike in former studies where the maximum coverage for one single complexation step was about 30%, we now observe a coverage twice as large, namely 60% of a full monolayer.…”
supporting
confidence: 80%
“…In situ STM has also been employed to characterize the structure of the electrodeposited Pd on the 4-ATP adlayer, as shown in Figure 2c. Like in former studies on Pd overlayers on top of 4-mercaptopyridine SAMs, [7,8,13,14] monoatomic height islands are seen in line-scans (not shown here), which finally can be assigned to Pd islands on top of the 4-ATP adlayer (see below). However, unlike in former studies where the maximum coverage for one single complexation step was about 30%, we now observe a coverage twice as large, namely 60% of a full monolayer.…”
supporting
confidence: 80%
“…[81] In addition, examination of molecules on conductors with photoelectron spectroscopy has shown that the orbital energies and tunneling barrier derived from them can be significantly modified by broadening and electronic coupling with the contacts. [7,116] An elegant application of a mesoscale cpAFM experiment appeared recently, for the case of conjugated molecules of variable length. [82] A layer by layer synthesis produced oligophenyleneimine (OPI) molecules of various lengths bonded to Au through a thiolate linkage (Fig.…”
Section: Progress With Mesoscale Molecular Junctionsmentioning
confidence: 99%
“…The principle has been demonstrated for uniform thiol SAMs featuring tail groups which coordinate metal ions [74][75][76][77][78][79]. Upon reduction of the ions the metal forms 2D or 3D clusters on top of the SAM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if the ions are discharged at the outer surface of the SAM which is accomplished by coordinating the ions to the terminal group of the SAM, the neutral metal species do not penetrate but diffuse at the SAM/electrolyte interface to form 2D islands and 3D clusters on top of the SAM [74][75][76][77][78][79].…”
Section: Page 17 Of 35mentioning
confidence: 99%